Feeds and forages intervention strategies for improved livestock nutrition and productivity in the Northwest Highlands of Vietnam - Otieno, Mary Atieno; Bùi, Van Tung; Phan, Huy Chuong; Trần, Thi Bich Ngoc; Mai, Thanh Tu; Duncan, Alan J.; Douxchamps, Sabine; Peters, Michael (International Grassland Congress 2023, 2023)
Livestock production in Vietnam is critical for livelihoods particularly for ethnic minorities in the Northwest Highlands (NWH). Improved livestock management and productivity can be achieved through better feed management and increased cultivation of improved forages, to meet animal nutrition demand. This study aimed at assessing feed intervention strategies to address context-specific feed related challenges, mainly winter feed shortage in Mai Son district, Son La province, Vietnam. Feed interventions included promotion of improved forages (grasses and legumes) and capacity building on animal nutrition techniques including feed preservation, feed mix and feeding regimes for cattle and pigs. Willing farmers selected from a list of improved forages, were provided with seeds and planting materials, and guided on forage planting, management, and utilization. Farmers reported increased awareness on feed technologies, increased yield, and availability of high-quality feed for their livestock, as well as challenges encountered in forage utilization. Initial results from this study show the potential of feed and forage technologies in improving livestock productivity and lays a foundation for scaling these interventions in Vietnam.